Student academic alert system / Lee Foo Yee - Lee , Foo Yee (2003)
The main objective of this project is to develop a web-based academic alert system to identify students in University of Malaya (UM) who is having serious academic difficulties due to excessive societies activities of residential college’s project before it is too late to remedy these difficulties. This system allows students to propose the program or activities that they want to organize to the administrator of society, residential college and Student Affair Department of University of Malaya(HEP-Hal Ehwal Pelajar) to approve their proposal before they can start their project or activities. An alert will asked to resubmit the program proposal form if the system checked that one of the project team member are not qualified to take part in the program due to his or her CGPA is less that 2.0 and involved in different program currently. An academic alert can be initiated either by an administrator of society or residential college The administrator of Student Affair Department of UM. HEP-Hal Ehwal Pelajar will use this system to check the completeness of the proposal and decide whether to approve the proposal or not. Besides, this system able to store, track and view is consist of administrator of HEP, administrator of residential college and students from all faculty in UM. Waterfall model with prototyping has been chosen for this project because this model allows all or part of system to be constructed quickly to understand or to clarify issues. This system is developed on Microsoft SQL Server 2000 database. It is believed that this system would be beneficial to everyone inclusive of the administrator of HEP, administrator of society or residential college and students from all faculty in University of Malaya in the future.